Community changes in Zooplankton and Macrobenthos of a prawn culture field in relation to hydrographical conditions - Shreeram Sudheer Gubba (Department of Fishery Hydrography, College of Fisheries, 2003)
The present study was carried out in the prawn filtration field of the College of Fisheries at Panangad adjacent to the Cochin backwater system to find out the faunal variations of zooplankton and macrobenthos and to correlate them with the variations in hydro graphic conditions and compare the results with those obtained from the observations in the adjacent lake. Monthly samples for hydro graphical and biological studies were collected during the period from November 2002 to July 2003 from the culture field and adjacent backwater. Hydrographical features like temperature, salinity, transparency, pH, total alkalinity, dissolved oxygen, nitrate-N, phosphate-P, silicate-Si were observed. Crustacean larvae, copepods, tintinnids, nematodes, rotifers and veliger larvae of molluscs were the zooplankton groups obtained in the present study. Crustacean larvae and copepods were the dominant groups in both places and were found during all the months whereas tintinnids and nematodes were observed during saline period and their number decreased with decreasing salinity. Rotifers were recorded during low saline period only. Veliger larvae were recorded during December and February in the culture field, whereas, they were not present in the samples form the adjacent backwater. Statistical analysis for the influence of hydrographical parameters on the zooplankton showed that none of these had significant influence independently and the variations in the zooplankton abundance may be due to the combined effect of all these factors. Even though the seasonal changes in the total zooplankton were not pronounced the per cent composition of different groups showed fluctuation. Tanaidaceans, gastropods, polychaetes, amphipods, bivalves, isopods and chironomid larvae were the benthic groups obtained. Among these